Imported Malaria: a retrospective study in University Hospital, Kuala Lumpur, a ten-year experience - Jamaiah, I.; Anuar, A.K.; Najib, N.A.; Zurainee, M.N. (Malaysian Medical Association, 1998)
Over a period of ten years (1983-1992), 134 malaria cases admitted to University Hospital, Kuala Lumpur (UHKL) were analysed. Malays constituted 27.6, Chinese 29.8, Indians 9.7, Indonesians 16.4 and other foreigners 16.4. Therefore, of the total number of cases, foreigners constituted 32.8 (44) of all the malaria cases admitted to UHKL. Fifteen of these foreigners had chloroquine-resistant strains of malarial parasites. Three species of malaria were reported of which Plasmodium falciparum constituted the most (46.3) (80 of these developed resistance to chloroquine). Plasmodium vivax was confirmed in 44.8 (10 of these developed resistance to chloroquine) and there was only one case of Plasmodium malarie infection.